Clinical and Virological Factors Influencing the Performance of a NS1 Antigen-Capture Assay and Potential Use as a Marker of Dengue Disease Severity - Duong, Veasna; Ly, Sowath; Lorn Try, Patrich; Tuiskunen, Anne; Ong, Sivuth; Chroeung, Norith; Lundkvist, Ake; Leparc-Goffart, Isabelle; Deubel, Vincent; Vong, Sirenda; Buchy, Philippe (PLoS neglected tropical diseases, 2011)
Detection of dengue NS1 antigen in acute infection has been proposed for early diagnosis of dengue disease. The aim of this study was to evaluate the clinical and virological factors influencing the performance of the Platelia NS1 Ag kit (BioRad) and to assess the potential use of NS1 antigen and dengue viral loads as markers of dengue disease severity. Blood specimens were collected from patients hospitalized at the Kampong Cham hospital during the 2006 and 2007 dengue epidemics in Cambodia. Dengue infection was confirmed in 243/339 symptomatic patients and in 17 asymptomatic individuals out of 214 household members tested. Overall sensitivity and specificity of Platelia NS1 Ag kit were 57.5% and 100% respectively. NS1 Ag assay combined with IgM antibody capture ELISA significantly increased the sensitivity for dengue diagnosis. NS1 Ag positivity rate was found significantly higher in DF than in DHF/DSS, in primary than in secondary infections, in patients with a high viremia (>5 log/mL) and in patients infected with DENV-1. In asymptomatic individuals, the NS1 Ag capture sensitivity tends to be lower than that in symptomatic patients. Milder disease severity was observed independently in patients with RNA copy number >5 log10 cDNA equivalents/mL or in high level of NS1 antigen ratio or in DENV-1 infection. Overall sensitivity of NS1 Ag detection kit varied widely across the various forms of dengue infection or disease. Sensitivity was highest in patients sampled during the first 3 days after onset of fever, in patients with primary infection, DENV-1 infection, with high level of viremia and in DF rather than DHF/DSS. In asymptomatic patients, RT-PCR assay has proved to be more sensitive than NS1 antigen detection. The NS1 antigen level correlated significantly with viremia and a low NS1 antigen ratio was associated with more severe disease.